PERAN PARTAI POLITIK TERHADAP PEMILIHAN GUBERNUR KALIMANTAN TIMUR 2018 TERKAIT DASAR HUKUM UNDANG-UNDANG PARTAI POLITIK NOMOR 10 TAHUN 2016 TENTANG PEMILU KADA - Isnawati, Isnawati (Universitas 17 Agustus 1945 Samarinda, 2017)
This research is willing to know about the role of the political party to the general election of the governor as the head of the province in East Kalimantan 2018 based on the regulation No.10,2016 about the general election of the heads of the regional either the couple governor, mayor or regent in Indonesia. The method of the research is qualitative by library research.The essential content of the general election regulation is democratic mechanism. The result of the research is that one of the political party in here Indonesia Struggle Democratic Party (PDI Perjuangan) announced by the chairman of the winning team, Verdiana, that (1).Who will register to be the candidate through this party has to register himself or herself by paying such an amount of money to show the seriousness to the candidate but she does not determine how much money to pay Â and the requirements to fill out, (2).Besides the register payment there are some other requirements which are not yet explained.The suggestions are (1).The sum of the money to pay of te registeration has to be determined before , (2).The other requiements has to be declared soon